Identifikasi model ruang bermain anak TK di Kota Samarinda sesuai kurikulum 2013 tentang lingkungan alam - Rosalina, Sherly Vernanda; Sugianthara, Anak Agung Gede; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019, 2019)
Identify on model of kindergarten playground in Samarinda City based on curriculum 2013 about environmental education. This research is motivated by the absence of data from the identification of children's kindergarten play area in three kindergarten located in Samarinda City, namely TK Kartika V-11, TK Tunas Mulia and TK Islam Bunga Bangsa. This study aims to provide data on park quality and activities of hardscape and softscape implementation at Kindergarten locations. This study uses supporting data from the 2013 early childhood curriculum on the natural environment. The research method used survey method with data collection technique through observation, literature study, interview and questionnaire to respondent. The results of the analysis showed the identification data of children playground model so that it can then be compared with the conformity with the standard quality of McDowell and McDowell Criteria (1998) and Stigsdotter and Grahn (2002) with the modification format with Key Perfomance Index (KPI) according to Arifin, et al (2008). The assessment stage in the park was done on park elements, implementation and user activities by confirming the respondent and verifying park users against the location. The stages of this research were to produce recommendation of identification result from three kindergarten locations as descriptive recommendation and to produce better perception of application on children play room model according to the 2013 early childhood curriculum about knowledge in introducing natural environment.